Recent advances in dopant-free organic hole-transporting materials for efficient, stable and low-cost perovskite solar cells. Issue 9 (28th July 2022) - Yan, Pengyu; Yang, Daobin; Wang, Hongqian; Yang, Shuncheng; Ge, Ziyi
Abstract : This article reviews important advances in dopant-free organic hole-transporting materials for efficient and stable perovskite solar cells since 2020. Abstract : Perovskite solar cells (PSCs) have made huge progress with a record power conversion efficiency of up to 25.8% (certified 25.5%) in the last decade. Hole transporting materials (HTMs) are essential for obtaining high-efficiency PSCs which play a crucial role in extracting and transporting holes from the perovskite layer to the electrodes. To date, only two HTMs have led to the state-of-the-art performance in PSCs, namely, 2, 2′, 7, 7′-tetrakis[ N, N -di(4-methoxyphenyl)amino]-9, 9′-spirobifluorene (Spiro-OMeTAD) and poly[bis(4-phenyl)(2, 4, 6-trimethylphenyl)amine] (PTAA). However, these HTMs have a few drawbacks in terms of commercialization, including high production costs, and the need for hygroscopic dopants which deteriorate the long-term stability of PSC devices. Herein, this article reviews the great progress of dopant-free HTMs for PSC devices in the past two years, outlining the reports of chemical structures with promising properties toward achieving effective HTMs for devices with long-term stability. In particular, HTMs are classified based on the different perovskite materials, in contrast to the previous reviews that categorized the HTMs according to molecular structures or device architectures. Finally, detailed conclusions and outlooks of dopant-free HTMs toward commercial application are provided. We hope that this review can attract more attention and attempts to develop more low-cost dopant-free HTMs for highly efficient and stable PSCs.